The Effect of Patikan Kebo (Euphorbia hirta) Herbal Extract on Collagen Levels in the Kidney and Heart of Fibrotic Rats - Pahmi, Khairil; Rahim, Adelia Riezka; Musanip, Musanip; Sahrul Hudha, Lalu; Triani, Eva; Halim, Amran (Jurusan Farmasi Universitas Negeri Gorontalo, 2025)
Noncommunicable diseases (NCDs) are the leading cause of death worldwide. There are around 36 million deaths every year. An example of NCD, a non-communicable disease, is hypertension. Excessive consumption of sodium chloride (NaCl) is the main factor that can cause hypertension and organ fibrosis. A natural ingredient that has the potential to act as an antifibrosis agent against fibrosis is quercetin by increasing PPAR-Î³ expression. Based on research, one of the plants that contains quercetin is the herb of Patikan Kebo (Euphorbia hirta Linn). Collagen is a protein biomarker of fibrosis synthesized via the PPAR-Î³ signaling pathway. The aim of this research was to determine the organ protective effect of administration of Patikan Kebo herbal extract against renal fibrosis and heart in Wistar rats (Rattus norvegicus) induced with 1.5% NaCl. The method involved 15 male Wistar rats aged 2.5 months with a body weight of 100-150 grams, which were divided into three groups (KI: control; KII: induced by 1.5% NaCl; KIII: induced by 1.5% NaCl + Patikan Kebo extract 200 mg/kg body weight. The induction was carried out for 8 consecutive weeks. On day 56, the kidneys and heart were removed in groups I and II, while in group III the treatment with the Patikan-Kebo extract from Patikan-Kebo at a dose of 200 mg/kg body weight was continued for 28 days in Group III. Specifically, for group III, kidneys and heart were collected on day 84 after treatment with Patikan kebo extract on day 84. Collagen was stained with Giemsa stain. Data were analyzed using a Kruskal-Wallis test. The difference is considered significant if the probability value is p0.05. The result showed that there were significant differences between the control and treatment groups. Patikan Kebo extract can reduce collagen in rats with induced fibrosis with 1.5% NaCl.